FUNGSI SOSIAL RUANG PUBLIK (Studi Kasus Ruang Tepi Laut Kota Makassar) - Zakaria Ibrahim; Rahmat Muhammad; Sawedi Muhammad (Jurnal Ilmiah Global Education, 2023)
This research is motivated by urban waterfront spaces that are experiencing changes in social function, from shared living spaces to private spaces to become a handful of people who are economically capable. This study aims to determine the social function of waterfront space in Makassar City. This research uses a qualitative approach with a case study type. Data collection was carried out through in-depth interviews, participatory observation and documentation. Handling of informants follows a purposive procedure, namely determining in advance the group of informants who will be used as data sources with certain criteria. The informants of this study consisted of the indigenous people of the city of Makassar, immigrant communities and urban spatial planning experts. The results of this study indicate that the city's waterfront space which was previously a space for living together, a place for fishing boats to dock and dock, a place for welcoming families out to sea, a place for bargaining for fish buyers, has now become largely privatized for capital accumulation. The daily activities of fishing communities, which are a social function of the waterfront, are increasingly fading along with the management of coastal space as a tourist spot. Spaces that used to be easily accessible, time-free, cost-free have now been turned upside down. These spaces are now only accessible to social classes who have economic ability. As a beachside public space, its social function is disrupted because not all levels of society can access it. As a result, socio-economic class is quite difficult because it requires a lot of money. Waterfront public space has been socially degraded based on economic capacity.